2005
DOI: 10.3233/jad-2005-7401
|View full text |Cite
|
Sign up to set email alerts
|

In situ characterization and mapping of iron compounds in Alzheimer's disease tissue

Abstract: There is a well-established link between iron overload in the brain and pathology associated with neurodegeneration in a variety of disorders such as Alzheimer's (AD), Parkinson's (PD) and Huntington's (HD) diseases [1]. This association was first discovered in AD by Goodman in 1953 [2], where, in addition to abnormally high concentrations of iron in autopsy brain tissue, iron has also been shown to accumulate at sites of brain pathology such as senile plaques [3]. However, since this discovery, progress in un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 18 publications
4
67
0
Order By: Relevance
“…Iron elevation in AD brains, first demonstrated in 1953 [99], is a consistently reported finding [99][100][101][102][103][104][105][106][107][108]. Neuronal iron deposition causes oxidative stress via the Fenton reaction, which might contribute to elevated oxidative stress observed in the AD brain [109].…”
Section: Ironmentioning
confidence: 97%
“…Iron elevation in AD brains, first demonstrated in 1953 [99], is a consistently reported finding [99][100][101][102][103][104][105][106][107][108]. Neuronal iron deposition causes oxidative stress via the Fenton reaction, which might contribute to elevated oxidative stress observed in the AD brain [109].…”
Section: Ironmentioning
confidence: 97%
“…34 Because SWI lacks chemical sensitivity, the interpretation of SWI image intensity may be improved through comparison with the XAS maps of metals. In addition, the high resolution achievable with XAS imaging may uncover new information about the co-localization and deposition of different metals, and about pathways of metal storage in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Later that same year, Collingwood et al [62,63] demonstrated the application of this technique to AD tissue sections. This work provided the first map of iron distribution in AD tissue in which specific iron anomalies (areas of high iron concentration) were not only located but characterized with 5 lm spatial resolution.…”
Section: Iron-containing Compounds Related To Alzheimer Diseasementioning
confidence: 99%